Bioimpedance analysis parameters and epicardial adipose tissue assessed by cardiac magnetic resonance imaging in patients with heart failure - Dösch, Christina; Süselbeck, Tim; Leweling, Hans; Flüchter, Stephan; Haghi, Dariusch; Schönberg, Stefan; Borggrefe, Martin; Papavassiliu, Theano (Obesity, 2010)
There is increasing evidence that body composition should be considered as a systemic marker of disease severity in congestive heart failure (CHF). Prior studies established bioelectrical impedance analysis (BIA) as an objective indicator of body composition. Epicardial adipose tissue (EAT) quantified by cardiac magnetic resonance (CMR) is the visceral fat around the heart secreting various bioactive molecules. Our purpose was to investigate the association between BIA parameters and EAT assessed by CMR in patients with CHF. BIA and CMR analysis were performed in 41 patients with CHF and in 16 healthy controls. Patients with CHF showed a decreased indexed EAT (22 ± 5 vs. 34 ± 4 g/m2, P < 0.001) and phase angle (PA) (5.5° vs. 6.4°, P < 0.02) compared to healthy controls. Linear regression analysis showed a significant correlation of CMR indexed EAT with left ventricular ejection fraction (LV-EF) (r = 0.56, P < 0.001), PA (r = 0.31, P = 0.01), total body muscle mass (TBMM) (r = 0.41, P = 0.001), fat-free mass (FFM) (r = 0.30, P = 0.02), and intracellular water (ICW) (0.47, P = 0.0003). Multivariable analysis demonstrated that LV-EF was the only independent determinant of indexed EAT (P < 0.0001). Receiver operating characteristic curve analysis indicated good predictive performance of PA and EAT (area under the curve (AUC) = 0.86 and 0.82, respectively) with respect to cardiac death. After a follow-up period of 5 years, 8/41 (19.5%) patients suffered from cardiac death. Only indexed EAT <22 g/m2 revealed a statistically significant higher risk of cardiac death (P = 0.02). EAT assessed by CMR correlated with the BIA-derived PA in patients with CHF. EAT and BIA-derived PA might serve as additional prognostic indicators for survival in these patients. However, further clinical studies are needed to elucidate the prognostic relevance of these new findings.